Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms22095023
|View full text |Cite
|
Sign up to set email alerts
|

A New Protocol of Computer-Assisted Image Analysis Highlights the Presence of Hemocytes in the Regenerating Cephalic Tentacles of Adult Pomacea canaliculata

Abstract: In humans, injuries and diseases can result in irreversible tissue or organ loss. This well-known fact has prompted several basic studies on organisms capable of adult regeneration, such as amphibians, bony fish, and invertebrates. These studies have provided important biological information and helped to develop regenerative medicine therapies, but important gaps concerning the regulation of tissue and organ regeneration remain to be elucidated. To this aim, new models for studying regenerative biology could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 47 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…The involvement of circulating hemocytes in cell-mediated immune responses and the synthesis of immune-related molecules has already been confirmed in P. canaliculata [13,15,21,28,36]. As the number of physiological responses regulated by, or associated with, immune-related cells and molecules is increasing [37], the focus of subsequent experiments has been to investigate whether the chemical depletion of phagocytic immune-related cells could affect complex organ regeneration, in the absence of a specific immune challenge [11,38]. In previous experiments, it was demonstrated that adult P. canaliculata could regenerate the cephalic tentacle, and the presence of granular and large hemocytes therein was quantified via an in-house developed routine for semi-automated computer-assisted image analysis [11].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The involvement of circulating hemocytes in cell-mediated immune responses and the synthesis of immune-related molecules has already been confirmed in P. canaliculata [13,15,21,28,36]. As the number of physiological responses regulated by, or associated with, immune-related cells and molecules is increasing [37], the focus of subsequent experiments has been to investigate whether the chemical depletion of phagocytic immune-related cells could affect complex organ regeneration, in the absence of a specific immune challenge [11,38]. In previous experiments, it was demonstrated that adult P. canaliculata could regenerate the cephalic tentacle, and the presence of granular and large hemocytes therein was quantified via an in-house developed routine for semi-automated computer-assisted image analysis [11].…”
Section: Discussionmentioning
confidence: 98%
“…(D) Computerassisted hemocyte count in non-regenerating control, regenerating tentacles (12 hpa), and clodronate liposome-injected regenerating tentacles (12 hpa). Data from regenerating tentacles (12 hpa) have already been presented in a previous publication [11]; hence, they arereported in a different color. * p < 0.05 according to the Tukey-Kramer test.…”
Section: Clodronate Liposomes Affected the Timing Of Cephalic Tentacl...mentioning
confidence: 99%
See 1 more Smart Citation
“…The interest towards this model is due to its invasiveness [28], neurotoxicity [29], human parasite hosting [30] and observations about its capability to regenerate [31][32][33][34]. The systemic immune response in this snail involves circulating and tissue-resident haemocytes, together with different organs [11,16,[18][19][20][21]31,35,36]. The ampulla has been described as a capacious expansion of the anterior aorta, acting as a potential compensation chamber for the haemolymph when the animal is forced to retract into its shell [34].…”
Section: Introductionmentioning
confidence: 99%
“…Bergamini et al, 2021 [ 6 ] provided fascinating outcomes in their survey on a regenerative event in Pomacea canaliculata . They followed three months of the regeneration process for an adult cephalic tentacle, normally used in food searching, co-specific recognition and orientation.…”
mentioning
confidence: 99%